PERBANDINGAN PERFORMA KEKUATAN MAKSIMAL (1RM) PADA LATIHAN ANGKAT BEBAN ANTARA TIME-RESTRICTED FEEDING 16:8 DAN KONDISI TANPA PUASA INTERMITEN - Restu Zagi Firmansyach; Moh. Aidh Alghifari; Bagus Arifullah; Bahrul Ulum; Fairus Hakim Nurrohman; Zaidan Maulana Zaki (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2026)
Weight training performance, particularly maximal strength, is strongly influenced by energy availability and meal-timing strategies. Intermittent fasting (IF), especially the time-restricted feeding (TRF) method, has been widely adopted; however, its effects on maximal strength remain mixed. This study aimed to analyze differences in maximal muscle strength performance, measured using the One Repetition Maximum (1RM) deadlift, between Intermittent Fasting (IF) and Non-Intermittent Fasting (Non-IF) conditions in weightlifting athletes. The study employed a quasi-experimental design with a within-subject repeated-measures approach. The participants were 10 male weightlifting athletes aged 19–22 years. All participants underwent two treatment conditions sequentially: training under the Non-IF condition and training under the IF condition using a 16:8 TRF protocol. Maximal muscle strength was assessed using the 1RM deadlift test. Data were analyzed using a paired-samples t-test with SPSS at a significance level of α = 0.05. The results showed that the mean 1RM value in the Non-IF condition (46.78 ± 7.54 kg) was higher than in the IF condition (41.67 ± 6.79 kg). Statistical testing indicated a significant difference between the two conditions (p < 0.001). Weight training performed in a non-fasting state (Non-IF) produced better maximal strength performance than training performed under intermittent fasting. Meal timing prior to training should be considered an important factor in efforts to optimize athletes’ maximal strength.